Grain size and lattice parameter's influence on band gap of SnS thin nano-crystalline films - Gupta, Yashika (2016)
Tin sulphide nano-crystalline thin films were fabricated on glass and Indium Tin Oxide (ITO) substrates by thermal evaporation method. The crystal structure orientation of the films was found to be dependent on the substrate. Residual stress existed in the films due to these orientations. This stress led to variation in lattice parameter. The nano-crystalline grain size was also found to vary with film thickness. A plot of band-gap with grain size or with lattice parameter showed the existence of a family of curves. This implied that band-gap of SnS films in the preview of the present study depends on two parameters, lattice parameter and grain size. The band-gap relation with grain size is well known in the nano regime. Experimental data fitted well with this relation for the given lattice constants. The manuscript uses theoretical structure calculations for different lattice constants and shows that the experimental data follows the trend. Thus, confirming that the band gap has a two variable dependency.